Hegel, Tocqueville e a eticidade moderna - Moraes, Felipe Moralles e (Revista Eletrônica Estudos Hegelianos, 2020)
This article shows that Hegel and Tocqueville's thoughts stem from the same philosophical problem about the fragmentation of modern society and that they can be understood in a complementary way. It is argued that, on the one hand, the Hegelian theory of ethical life clarifies the Tocquevillean conception of freedom and that, on the other hand, Tocquevillean political sociology serves as a bridge between the ethical life theory and the democratic institutions. For both thinkers, the approach of modern society must be historical or sociological and reveal an immanent rationality in it, although Hegel better elaborated conceptually the idea of freedom, while Tocqueville presents it within the social and political framework of liberal democracy.